NEW GLYCAEMIC TARGETS- TIME TO LOOK BEYOND HBA1C: A REVIEW - Dr. Vipul Gupta; Dr. Girish Khurana (Medico Research Chronicles, 2019)
Diabetes is a condition defined by elevations in glucose. Historically, glucose measured in the fasting state or glucose measured two hours after a carbohydrate challenge (oral glucose tolerance test) have been the standard measures used to diagnose diabetes. Apart from this the researchers also reported various other shortcomings of measurement of blood glycemic value by HbA1c. A1C is a poor indicator of what occurs in the postprandial state. A1C captures only chronic hyperglycemia. Developed societies in which diabetes diagnosis is made with A1C and less developed societies (between and within countries) in which diabetes diagnosis is made with plasma glucose: such a division should be avoided. It would add to the inequities in health and health care. The objective of this article is to elaborate the uses of some nontraditional markers of hyperglycemia like 1. Fructosamine 2. Glycated albumin 3. 1,5-anhydroglucitol 4. Continuous glucose monitoring to be taken into consideration for estimation of blood glucose level as an alternative for HbA1c level determination.